Changing land use / land cover around an urban estuary : implications for ecosystem functioning - Jack, Sam (Department of Biological Sciences, 2017)
The changing spatial and temporal patterns in land use/land cover surrounding Zandvlei estuary were investigated over the period 1944 to 2005. Changes in the extent of four terrestrial and two aquatic land use/land cover categories were mapped from high quality aerial photographs using ArcView GIS. Basic spatial analyses were performed to quantify changes in area, 'edge-effects' and relative dominance through time. Semi-natural and seasonally inundated classes accounted for over 70% of land cover in 1944, but declined steadily as urban land use and permanently inundated land cover expanded to a present-day extent of 42% and 19% respectively. The following major drivers of change were identified: 1) the construction of the railway embankment bisecting Westlake wetland and Zandvlei estuary, which led to sedimentation and a change in plant species composition of the wetland, but decreased nutrient inflows into the vlei; 2) agricultural practices within the catchment at the start of the 20th century which increased sediment and nutrient inflows; 3) elevated water levels due to dredging operations between 1947 and 1961, which resulted in a significant loss of seasonally inundated land cover with concomitant changes in species composition and nutrient dynamics; and 4) urban development surrounding the vlei (with particular reference to Marina da Gama), which has expanded at the expense of semi-natural areas and significantly increased effluent and litter inputs into the vlei. A socially and ecologically balanced management policy governing the entire catchment is required to mitigate future impacts.